Increased coiling frequency linked to apoptosis in the brain and altered thyroid signaling in zebrafish embryos (Danio rerio) exposed to the PBDE metabolite 6-OH-BDE-47 - Wang, Feng (2018)
Polybrominated diphenyl ethers (PBDEs) are a group of brominated flame retardants that are ubiquitously detected in the environment and associated with adverse health outcomes. 6-OH-BDE-47 is a metabolite of the flame retardant, 2,2′,4,4′-Tetrabromodiphenyl ether (BDE-47), and there is increasing concern regarding its developmental neurotoxicity and endocrine disrupting properties. In this study, we report that early life exposure in zebrafish (Danio rerio) embryos to 6-OH-BDE-47 (50 and 100 nM) resulted in higher coiling frequency and significantly increased apoptotic cells in the brain. These effects were partially rescued by overexpression of thyroid hormone receptor β (THRβ) mRNA. Moreover, exposure to 100 nM 6-OH-BDE-47 significantly reduced the number of hypothalamic 5-hydroxytryptamine (5-HT, serotonin)-immunoreactive (5-HT-ir) neurons and the mRNA expression of tryptophan hydroxylase 2 (TPH2). These results indicate that 6-OH-BDE-47 affected thyroid hormone regulation through THRβ and negatively impacted the nervous system, in turn, affecting coiling behavior. Correlations of these endpoints suggest that coiling frequency could be used as an indicator of neurotoxicity in embryos.